Peran Pemerintah Desa dalam Mengurangi Pengangguran di Desa Loru Kecamatan Sigi Biromaru - Adriawan Zakaria; Betty Betty (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This activity aims to find out and describe the extent of the Government's Role in Overcoming Unemployment in Loru Village, the causes of unemployment, types of unemployment, government participation in reducing unemployment and benefits for all parties who are no longer unemployed/have found work. Methods of implementation using the method of observation, interviews, place and time of research. The results of this activity indicate that the Government's role is significantly very influential on unemployment. The government must play an active role because there are still many qualified graduates who have not yet found decent jobs, and must pay more attention to the unemployed, such as providing skills or abilities in the world of work, so that there are no more unemployed people in Loru Village.